Comparative secondary metabolites profiling and biological activities of aerial, stem and root parts of Salvadora oleoides decne (Salvadoraceae). Issue 23 (1st December 2020) - Saleem, Hammad; Ahmad, Irshad; Zengin, Gokhan; Mahomoodally, Fawzi M.; Rehman Khan, Kashif-Ur-; Ahsan, Hafiz Muhammad; Abidin, Syafiq Asnawi Zainal; Ahemad, Nafees
Abstract: In this study, different parts (aerial, stem and root) of Salvadora oleoides Decne were investigated in order to explore their phytochemical composition and biological potential. The bioactive contents were evaluated by conventional spectrophotometric methods. Additionally, the secondary metabolite compounds were identified by UHPLC-MS analysis. Biological potential was evaluated by determining antioxidant (DPPH, FRAP, and Phosphomolybdenum) and enzyme inhibitory (butrylcholinesterase and lipoxygenase) effects. Higher total bioactive contents were found in methanolic extracts which tend to correlate with higher radical scavenging and reducing potential of these extracts. LC/MS spectrum revealed the presence of 16 different secondary metabolites belonging to terpene, glucoside and sesquiterpenoid dervivatives. Glucocleomin and emotin A were the main compounds present in all three parts. The strongest butrylcholinesterase and lipoxygenase inhibitory activity was observed for root and stem DCM extracts. Demonstrated biological potential of S. oleoides plant can trace a new road map for developing newly designed bioactive pharmaceuticals. Abstract :